Influence of soil factors on population dynamics of bioagent -Trichoderma harzianum - Y.S. PAUL, MEENA DEVI* and (Indian Phytopathology, 2008)
Population dynamics of Trichoderma harzianum (JMA-4), the best identified isolate against pea root rotJ wilt complex was studied at different moisture, temperature and pH levels up to 60th day of inoculation. The maximum population (71.0x 106 cfu/g soil) was noticed at 35 per cent followed by 30 per cent moisture. Temperature of 25Â°C was found to be the most suitable for multiplication whereas higher temperatures (30- 35Â°C) inhibited the growth of bioagent. The highest population( 142.3x 106 cfu/gsoil) was recorded at pH 6.6 followed by 5.4 pH. Alkaline pH inhibited the multiplication of T. harzianum.